Parental volunteering in schools: perspectives from a Central and Eastern European region - Hajnalka Fényes; Zsolt Csák; Gabriella Pusztai (Cogent Education)
This study makes a novel contribution by quantitatively comparing maternal and paternal volunteering in schools—an often-overlooked dimension of parental involvement in Central and Eastern Europe. Drawing on a large-scale questionnaire survey conducted among parents of primary and secondary school students in the cross-border region of Hungary, Romania, and Ukraine, the analysis employs linear regression models to identify factors influencing parental volunteering. The results show that among interviewed parents, fathers' volunteering rates were comparable to those of mothers, whereas among non-interviewed (partner) parents, mothers were significantly more often reported as school volunteers. Consistent with the dominant status model of volunteering, additional individual characteristics were also found to be associated with engagement. Volunteering was more common in primary schools and in institutions maintained by churches or foundations. The findings underscore the critical role of schools in promoting parental involvement, particularly among fathers. Encouraging father-inclusive volunteering practices, especially in underperforming or state-run schools, could help advance educational equity, strengthen social cohesion, and support children's development. These insights are especially pertinent in the post-pandemic context of rebuilding trust and community around educational institutions.